SISTEM ZAKAT DI NEGARA MAROKO - Syukry El Hanif Nasution; Maryam Batubara (Smart Education, 2026)
Abstract: This study aims to analyze the zakat management system in Morocco by comparing it with institutional zakat models in other Muslim countries such as Indonesia and Malaysia. The research uses a literature review method by examining various secondary sources including national and international scientific journals indexed in SINTA, Scopus, and Web of Science, as well as theses and dissertations from university repositories. The study focuses on institutional aspects, collection mechanisms, and zakat distribution along with their implications for poverty alleviation effectiveness. The results show that zakat practices in Morocco are still voluntary and not supported by a centralized institutional system, in contrast to countries such as Indonesia and Malaysia which have established official institutions and more structured management systems. This condition creates challenges in terms of transparency, accountability, and optimization of zakat distribution, thereby limiting its effectiveness in reducing poverty. In contrast, countries with centralized systems tend to have more efficient, coordinated, and measurable management. Therefore, this study recommends the establishment of a national zakat institution in Morocco that can integrate the collection and distribution processes in a professional, transparent, and accountable manner to enhance the role of zakat in social and economic development. Keywords: Zakat Morocco, Zakat Institution, Transparency, Accountability, Poverty Alleviation Abstrak: Penelitian ini bertujuan untuk menganalisis sistem pengelolaan zakat di Maroko dengan membandingkannya dengan model kelembagaan zakat di beberapa negara Muslim lain seperti Indonesia dan Malaysia. Penelitian menggunakan metode tinjauan pustaka atau literature review dengan mengkaji berbagai sumber sekunder berupa jurnal ilmiah nasional dan internasional yang terindeks SINTA, Scopus, dan Web of Science, serta tesis dan disertasi dari repositori universitas. Fokus kajian terletak pada aspek kelembagaan, mekanisme pengumpulan, serta distribusi zakat dan implikasinya terhadap efektivitas pengentasan kemiskinan. Hasil penelitian menunjukkan bahwa praktik zakat di Maroko masih bersifat sukarela dan belum didukung oleh sistem kelembagaan yang terpusat, berbeda dengan negara seperti Indonesia dan Malaysia yang telah memiliki lembaga resmi dan sistem pengelolaan yang lebih terstruktur. Kondisi ini menyebabkan tantangan dalam hal transparansi, akuntabilitas, dan optimalisasi distribusi zakat, sehingga efektivitasnya dalam mengurangi kemiskinan belum maksimal. Sebaliknya, negara dengan sistem terpusat cenderung memiliki pengelolaan yang lebih efisien, terkoordinasi, dan terukur. Oleh karena itu, penelitian ini merekomendasikan pembentukan lembaga zakat nasional di Maroko yang mampu mengintegrasikan proses pengumpulan dan distribusi zakat secara profesional, transparan, dan akuntabel guna meningkatkan peran zakat dalam pembangunan sosial dan ekonomi. Kata Kunci: Zakat Maroko, Kelembagaan Zakat, Transparansi, Akuntabilitas, Pengentasan Kemiskinan